The development of web based training for kids to learn music theory / Syafira Shamsuddin - Shamsuddin, Syafira (Faculty of Computer and Mathematical Sciences, 2007)
Nowadays, the web is frequently used as a platform for e-learning applications. These applications vary from static lecture presentations to fully integrated, dynamic multimedia applications that enabling interaction between student and lecturer. Through E-learning students can adapt the lesson efficiently as they can hear, see, and customize the lesson as they like. This thesis is about developing website training for kids to learn the music theory. The music subject lesson has been chosen in this project music education in Malaysia is not really emphasize. According to the research, quality of music education in Malaysia is still in low level since most of educators do not have enough knowledge. Furthermore, as music was only introduced on a wider scale in school about 23 years ago, many children in Malaysia do not received well music education. Moreover, the formal music educations are only introduced in primary school thus the potential of students to learn music in depth is very limited. Thus with this prototype hopefully could change the situation. Because music education actually can give many benefits for student such as in learning because they at the same time can practice using the left and the right brain .The lesson is focus on the beginner especially for the child including Piano Key Lesson, Piano Note Lesson and Line and Space Note Lesson. The scope of this project will focus only on content and syllabus that will be a path to Music Year 1 KBSR that have been provided by the Ministry of Education Malaysia. The main objectives from the development of the system are, to develop web based training software for kids to learn music theory, the prototype is produce by adapting the theory of constructivism in order to enhance student learning ability toward music theory and also to develop an interesting practice tools for kids to get familiar with the musical theory and concepts via Internet.